Exploring the Coordination of Cardiac Ion Channels With Action Potential Clamp Technique - Horváth, Balázs; Szentandrássy, Norbert; Dienes, Csaba; Kovács, Zsigmond M.; Nánási, Péter P.; Chen-Izu, Ye; Izu, Leighton T.; Banyasz, Tamas (Frontiers in Physiology, 2022)
The patch clamp technique underwent continual advancement and developed numerous variants in cardiac electrophysiology since its introduction in the late 1970s. At the beginning, the capability of the technique was limited to record one single current from one cell stimulated with rectangular command pulse. Since that time, the technique has been extended to record multiple currents under various command pulses including action potential. The current review summarizes the development of the patch clamp technique in cardiac electrophysiology with special focus on the potential applications in integrative physiology.